ANALISIS KINERJA KEUANGAN PADA PERUM BULOG KANWIL NTT - Tiffany N. P. Gah; Yunce Foes; Agusta Amanda Wulandari; Sri Endar Utami (JAKA - Jurnal Jurusan Akuntasi, 2021)
Information on the financial performance of Perum BULOG NTT Regional Office in the value of a company's financial level can be done by analyzing the company's financial statements. Knowing the company's financial condition is in good condition, various analyzes can be carried out, one of which is ratio analysis. The purpose of this study was to determine the financial performance of the Perum BULOG Regional Office of NTT by looking at the last two years before Covid 19 and two years of the occurrence of Covid 19.The analytical method used is descriptive analysis with a quantitative approach using the ratio of liquidity, profitability, activity and solvency. Data obtained from Perum BULOG NTT Regional Office from 2017 to 2020.Based on the average liquidity ratio Current Ratiois 38.07% and the Cash Ratio is 126%. The average solvency ratio of own capital to total assets is 37.64 %. The average activity ratio of Inventory Trun Over (ITO) is 127.5 %, total assets are trunt over (TATO) 9.08% and Average Collection Periods (ACP) is 395%. Profitability Ratio Return On Investment (ROI) 8, 98% and Return On Equity (ROE) 24.95%. The description above can be concluded that the company's financial performance is in a healthy condition with category A